The Quran As A Protector Of Self And Practice In Community - Shofa, Mu’arifatush; Iswanto, Agus (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstrack The Qur’an for the Muslim community is not only seen as a sacred text that is read, but is also used for various purposes, including as personal protection. This article is about to discuss about the verse or letter of the Qur’an as a means of protection (mageri) themselves according to the angry interpretation of the labid and the views of the people in etc. Cikalan against the Qur’an as a personal protector. The research combines library research and field research with descriptive analysis and using the living Qur'an approach. The results of this study indicate that the Qur'an can be used as a means of personal protection. The verses or Surahs that are often practiced by the public are Surah al Ikhlas, Surah al Falaq, Surah an Nas, Surah al Mulk and verse seats. The purpose of carrying out the practice of the Qur'an as self-protection is to obtain blessings, get used to reading the Qur'an and follow what the Prophet Muhammad taught. namely making the Qur'an as a stronghold, and every human being wants to be spafe from danger wherever they are, both when sleeping, staying at home and outside. The results of this study reinforce the view that the reception of the Muslim community towards the Qur’an varies, not only as a text that is read, but a text that is used in daily life. Keywords: Living Qur’an, Protector, Society Abstrak Alquran bagi masyarakat muslim tidak hanya dipandang sebagai sebuah teks sakral yang dibaca, tetapi juga digunakan untuk berbagai kepentingan, termasuk sebagai pelindung diri. Artikel ini hendak mendiskusikan tentang ayat atau surat Alquran sebagai sarana pelindung (mageri) diri menurut tafsir marah labid dan pandangan masyarakat di dusun Cikalan terhadap ayat Alquran sebagai pelindung diri. Penelitian menggabungkan penelitian kepustakaan (library research) dan penelitian lapangan (field research) dengan analisis deskriptif dan menggunakan pendekatan living Qur’an. Hasil penelitian ini menunjukkan bahwa Alquran bisa di gunakan sebagai sarana pelindung diri. Adapun ayat atau surat Alquran yang sering diamalkan oleh masyarakat yaitu surat al Ikhlas, surat al Falaq, surat an Nas, surat al Mulk dan ayat kursi. Tujuan pelaksanaan pengamalan Alquran sebagai pelindung diri tersebut adalah agar memperoleh berkah, membiasakan diri membaca Alquran dan mengikuti apa yang telah diajarkan Nabi Muhammad saw. yaitu menjadikan Alquran sebagai benteng pertahanan, serta setiap manusia menginginkan selamat dari bahaya dimana saja berada, baik ketika tidur, diam di rumah maupun di luar rumah. Hasil penelitian ini memperkuat pandangan bahwa resepsi masyarakat Muslim terhadap Alquran beragam, tidak hanya sebagai teks yang dibaca, tetapi teks yang difungsikan dalam kehidupan sehari-hari. Kata Kunci: Living Qur’an, Pelindung, Masyarakat